Trends in insect repellent formulations: A review - Tavares, Melanie; da Silva, Márcio Robert Mattos; de Oliveira de Siqueira, Luciana Betzler; Rodrigues, Raphaela Aparecida Schuenck; Bodjolle-d'Almeida, Lolita; dos Santos, Elisabete Pereira; Ricci-Júnior, Eduardo (International journal of pharmaceutics, 2018)
[Display omitted] The use of natural and synthetic repellents, marketed in different pharmaceutical forms, is growing in the world due to the emerging vector-borne viral diseases as Dengue, Zika, Chikungunya, Yellow Fever and Malaria. The choice of the ideal formulation will depend on a series of factors to be analyzed: type of repellent active (natural or synthetic), pharmaceutical forms (spray, lotion, cream, gel), action time duration (short or long), environment of exposure and the user (adult, pregnant women, children, newborn). The most used repellents are DEET, IR3535 (Ethyl Butylacetylaminopropionate) (EB), Icaridin (Picaridin) and essential oils, each of them presenting advantages and disadvantages. DEET is the oldest and the most powerful repellent available in the market, thus being the reference standard. For this reason, there are many classic formulations available in the market containing the chemical component DEET in spray forms and lotions. However, due to its toxicity, DEET is not recommended for children up to 6 months and pregnant women. DEET has been an option along with other market-shared products as IR3535 and Icaridin (Picaridin), which present less toxicity in their composition. IR3535 is the less toxic and may be prescribed for children over 6 months of age and pregnant women so that they have been the best option because of the lower toxicity levels presented. IR3535 is the one that has the lowest toxicity level among the three options and may be prescribed for children above 6 months of age and pregnant women. Icaridin is as potent as DEET, but less toxic, and has the advantage of having the long-lasting action among the aforementioned repellents. The new formulations have been based on controlled release systems (CRS). The CRSs for repellents comprise polymer micro/nanocapsules, micro/solid lipid nanoparticles, nanoemulsions/microemulsions, liposomes/niosomes, nanostructured hydrogels and cyclodextrins. There are many formulations based on micro and nanocapsules containing DEET and essential oils to increase repellent action time duration and decrease permeation and consequently, systemic toxicity. The development of new formulations for the IR3535 and Icaridin is a research field yet to be explored. The current trend is the use of natural repellent actives such as essential oils, which present low toxicity, do not harm the environment, but present reduced repellent action time due to rapid evaporation after skin application. CRSs have been used as vehicle of natural repellents to improve long-lasting repellent action, reduce skin permeation and systemic effects.